Odpowiedzi

2010-03-20T09:52:40+01:00
A)2(x-3)+3(4-x)=5
2x-6+12-3x=5
-x+6=5
-x=5-6
-x=-1 |*(-1)
x=1
b)3(x-4)-2(2x-5)=-4
3x-12-4x+10=-4
-x-2=-4
-x=-4+2
-x=-2 |*(-1)
x=2
c)2(x+4)-5(x+3)=2
2x+8-5x-15=2
-3x-7=2
-3x=2+7
-3x=9 |/(-3)
x=-3
d)-2(x+3)+4(2x+3)=-6
-2x-6+8x+12=-6
6x+6=-6
6x=-6-6
6x=-12 |/6
x=-2
2010-03-20T10:03:31+01:00
A) 2(x-3)+3(4-x)=5
2x-6+12-3x=5
2x-3=5+6-12
-1x=-1 I:-1
x=0

b) 3(x-4)-2(2x-5)=-4
3x-12-4x+10=-4
3x-4x=-4+12-10
1x=-2 I:1
x=2

c) 2(x+4)-5(x+3)=2
2x+8-5x-15=2
2x-5x=2-8+15
-3x=9 I:-3
x=2

d) -2(x+3)+4(2x-3)=-6
-2x-6+8x-12=-6
-2x +8x=-6+6+12
4x=12 I:4
x=3
2010-03-20T10:15:19+01:00
A)2x-6+12-3x=5
2x+3x=5+6-12
-1x=-1/: (-1)
X=-1
B)3x-12-4x+10=-4
3x-4x=-4+12-10
-1x=-2/: (-1)
X=-1
C)2x+8-5x-15=2
2x-5x=2-8+15
-3x=9/ : (-3)
X=-3
D)-2x+8x=-6+6-12
6x=-12
X=-6